Impacts of Nutrition and Feeding Programs on Farmers’ Management Decisions Affecting the Success of Dairy Farms with Culture Breed Cattle - Yavuz Topcu; Mehmet Toparlak; Muhlis Macit (Turkish Journal of Agriculture: Food Science and Technology)
The aim of the study is to evaluate all the factors determining the milk production and yield decisions with regard to the nutrition and feeding programs affecting the integrated management strategies on the success of the dairy farms with culture breed cattle under the pasture-based and indoor barn-based production systems. For these aims, data obtained from the individual interviews conducted at the dairy farms with 100 culture breed cattle were used for Principal Component and Multiple Regression Analyses. The results of the study highlighted that while there were linear positive relationships among liquid assets of farms value, concentrate feed and fodder intake of dairy cattle, milk sale price, forage crop support, additional feeding and their types at pasture and milk yields per dairy cattle at the dairy farms; there were inverse relationships among hay intake of dairy cattle, lactation period, pasture planning, culture breed cattle support and those. The farmers could increase the successes of the dairy farms by increasing the technical and economic effectiveness under the integrated management pattern approaches at those with culture breed cattle.